PERAN KEPALA DESA DILIHAT DARI ASPEK INTERPERSONAL DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI DESA RAMANIA KECAMATAN PATANGKEP TUTUI KABUPATEN BARITO TIMUR (p3m.stiatabalong.ac.id, 2022)
The Role of the Village Head Seen from the Interpersonal Aspect in Road Infrastructure Development in Ramania Village, Patangkep Tutui District, East Barito Regency (Case study on development in Ramania Village). Supervisor I H. Jamaluddin, SE, MAP. The village is essential in the Unitary State of the Republic of Indonesia. The village has existed since before the Republic of Indonesia was proclaimed on August 17, 1945. Even though the formation of Indonesia started from the countryside, the facts show that most of Indonesia's territory is rural. So the role of village heads will be significant if they are active in visiting the community, often attending meetings, and always explaining the benefits of village government programs; these community leaders are also active in inviting community members to manage activities. If the community sees their respected figures as participating in these activities, then the community will be interested in participating in road infrastructure development activities in the village. Therefore, the presence of the village head is essential in mobilizing the community to support the success of development, especially in the village. The purpose of this paper is to find out and analyze how the role of the village head is seen from the interpersonal aspect in the development of road infrastructure in Ramania village. This research method uses a descriptive approach with qualitative techniques—data collection techniques through observation and interviews accompanied by documentation. Based on the existing data, the author describes/describes in a systematic, factual, and accurate way about the facts and phenomena that exist. The results of this study indicate that the role of the village head is seen from the interpersonal aspect in development in Ramania village, Patangkep Tutui district, East Barito regency; the author can conclude with the results that it plays a significant role. Suggestion: To the village head, in order to be able to participate in the construction of road infrastructure, I realize that there are still many shortcomings in writing this thesis, and it is hoped that future research can improve this research. Keywords: The Role of the Village Head, Interpersonal Aspects, Road Infrastructure Development